Perbandingan Batas Usia Perkawinan di Negara-Negara Muslim Asia dan Afrika Utara: Kajian Yuridis dan Sosio-Kultural - Khoiroh, Ikmilul; A Hirzan Anwari; Fitriana Deva Yanti (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Abstract This study aims to examine the minimum age for marriage in Muslim countries in Asia and North Africa from a juridical and socio-cultural perspective, as well as to conduct a comparative analysis. The method used in this research is library research with a normative juridical approach, collecting data from relevant literature. The findings of this study indicate that the establishment of minimum marriage ages in Muslim-majority countries across Asia and North Africa reflects variations influenced by legal, social, cultural, and political factors. Indonesia stands out with the highest marriage age requirement, set at 19 years for both men and women. Other countries, such as Pakistan and Egypt, have lower minimum ages, with some setting different standards for males and females. Additionally, the differences in age requirements are often shaped by the dominant Islamic schools of thought (mazhab) in each country, such as the Shafi’i school in Indonesia and Malaysia, the Hanafi school in Pakistan and Turkey, and the Maliki school in Morocco. Countries like Turkey and Morocco have undergone legal reforms incorporating principles of secularization and gender equality. These legal reforms also seek to reduce divorce rates and improve family life quality. Notably, Pakistan is the only country in the study to impose legal sanctions on those who violate marriage age laws, while other nations, like Indonesia, rely on judicially supervised marriage dispensation regulations to address underage marriages. Abstrak Penelitian ini bertujuan mengkaji batas usia minimal pernikahan di negara-negara Muslim Asia dan Afrika Utara dari perspektif yuridis dan sosio-kultural, serta melakukan analisis perbandingan. Metode yang digunakan adalah library research, dengan pendekatan yuridis normatif. Hasil penelitian menunjukkan bahwa penetapan batas usia perkawinan di negara-negara Muslim Asia dan Afrika Utara bervariasi, dipengaruhi oleh faktor hukum, sosial, budaya, serta dinamika politik di setiap negara. Indonesia memiliki ketentuan usia perkawinan tertinggi, yaitu 19 tahun untuk laki-laki dan perempuan. Sementara itu, di negara lain seperti Pakistan dan Mesir, usia minimal perkawinan lebih rendah dengan beberapa negara menetapkan usia yang berbeda untuk laki-laki dan perempuan. Perbedaan ini juga dipengaruhi oleh mazhab yang dianut, seperti mazhab Syafi’i di Indonesia dan Malaysia, mazhab Hanafi di Pakistan dan Turki, serta mazhab Maliki di Maroko. Reformasi hukum di negara-negara seperti Turki dan Maroko juga mencerminkan adopsi prinsip-prinsip sekularisasi dan kesetaraan gender. Pakistan menonjol sebagai satu-satunya negara yang memberlakukan sanksi hukum tegas bagi pelanggar batas usia perkawinan, sedangkan negara lain seperti Indonesia mengandalkan regulasi dispensasi perkawinan yang diawasi oleh pengadilan. Keywords: Batas Usia Perkawinan; Negara Muslim; Asia; Afrika Utara